2011
DOI: 10.2174/092986711797379221
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Alterations and Neuropsychiatric Disorders

Abstract: Mitochondria are membrane-enclosed organelle found in most eukaryotic cells, where they generate the majority of the cell's supply of adenosine triphosphate (ATP), used as a source of chemical energy. In addition, they are involved in a range of other processes, such as signalling, cellular differentiation, cell death, as well as the control of the cell cycle and cell growth. Mitochondria have been implicated in several neuropsychiatric disorders, in particular, depression, anxiety, schizophrenia, autism, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 94 publications
1
26
0
Order By: Relevance
“…20, 33, 34, 35 Additionally, these selected genes are representative of different gene co-expression networks, based on our previous studies, which identified over 20 gene co-expression modules in the prefrontal cortex from subjects with schizophrenia and bipolar disorder. 36 We first tested for expression differences for five neuronally expressed genes, GABAergic neurotransmission: GAD1 ; mitochondrial function/import: TOMM70A ; neurotransmitter receptor signaling: serotonin 5-hydroxytryptamine receptor 2C ( HTR2C ) and regulator of G protein signaling 4 ( RGS4 ); signal transduction: protein phosphatase, Mg 2+ /Mn 2+ dependent, 1E ( PPM1E ) in the postmortem prefrontal cortex (Brodmann area 10) from a cohort of subjects with schizophrenia and bipolar disorder from the Harvard Tissue Resource Center (group 1; Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…20, 33, 34, 35 Additionally, these selected genes are representative of different gene co-expression networks, based on our previous studies, which identified over 20 gene co-expression modules in the prefrontal cortex from subjects with schizophrenia and bipolar disorder. 36 We first tested for expression differences for five neuronally expressed genes, GABAergic neurotransmission: GAD1 ; mitochondrial function/import: TOMM70A ; neurotransmitter receptor signaling: serotonin 5-hydroxytryptamine receptor 2C ( HTR2C ) and regulator of G protein signaling 4 ( RGS4 ); signal transduction: protein phosphatase, Mg 2+ /Mn 2+ dependent, 1E ( PPM1E ) in the postmortem prefrontal cortex (Brodmann area 10) from a cohort of subjects with schizophrenia and bipolar disorder from the Harvard Tissue Resource Center (group 1; Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…A growing body of evidence suggests that mitochondrial disturbances play a key role in the pathogenesis of depression [19, 31], but the impact of chronic tianeptine administration on the mitochondria-enriched subproteome in both the hippocampus and the frontal cortex in an animal model of depression had not been investigated so far. With regard to the hippocampus, the upregulated expression of isocitrate dehydrogenase (IDH) after chronic tianeptine administration appears to be the most striking finding of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety, fear and stress elicit high neuronal activity in distinct brain regions accompanied by high energy requirements, which mean a great demand for ATP. Mitochondria, which are the main cellular ‘power plants’ producing the large majority of ATP, are therefore crucial for efficient brain function, including the regulation of mood and anxiety 142 . The ability of cannabinoids to control mitochondrial activity was first reported in the 1970s 143 and is now thought to be a potentially important way in which eCBs influence cellular and brain functions 144,145 .…”
Section: Future Directionsmentioning
confidence: 99%